Hubungan Durasi Penggunaan Smartphone dengan Kejadian Tension-Type Headache pada Mahasiswa Keperawatan - Alatas, Sarah; Jusuf, Muhammad Isman; Hunowu, Sri Yulian (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the relationship between smartphone usage duration and tension-type headache incidence in nursing students at Gorontalo State University. The method used was quantitative with an observational analytical design and a cross-sectional approach. The results showed a p-value of 0.001 (<0.05), indicating a significant relationship between smartphone usage duration and tension-type headache incidence in nursing students at Gorontalo State University. In conclusion, the longer the smartphone usage duration, the higher the likelihood of experiencing tension-type headache. Keywords: Smartphone Usage Duration, Tension-Type Headache